TECHNOLOGIES FOR ACCELERATING PHARMACEUTICAL RESEARCH THROUGH COMPUTER MODELING - Normamatov Sardor; Islomov Farxod; Mirag'zamov Dilmurot (Modern American Journals, 2025)
This article explores the role of computer modeling technologies in accelerating pharmaceutical research. The process of drug development is typically complex, time-consuming, and requires substantial financial investment. In this context, computer modeling (in silico technologies) offers an effective means to optimize research procedures by predicting toxicological and pharmacological properties in advance. The study reviews key methods such as molecular docking, molecular dynamics, and QSAR modeling (Quantitative Structure-Activity Relationship). Furthermore, it analyzes the advantages and limitations of these technologies compared to traditional laboratory research, as well as their potential for real clinical applications. The article concludes with practical recommendations for implementing computer modeling technologies in Uzbekistan’s pharmaceutical industry.
Keywords: Computer modeling, pharmaceutical research, molecular docking, molecular dynamics, QSAR modeling, in silico methods, drug design, artificial intelligence, pharmacology, Uzbekistan pharmaceutical industry.